Watermelon (Citrullus Lanatus) Value Chain and Smallholder Livelihood Improvement in the Upper East Region of Ghana, - Bukari, B. (University of Ghana, 2014)
The study was conducted among one hundred and thirty (130) participants; 120 farmers and 10 buyers. The purpose of the study is to examine the production of watermelon as a high value crop in contributing to livelihood of smallholder farmers in the Bawku West District (BWD) in the Upper East Region (U/E/R) of Ghana. Specifically, the study sought to achieve the following objectives: to determine the relationship between personal characteristics of smallholders and level of participation in watermelon production, to determine the linkages and strengths among actors in watermelon production and to examine the contribution of watermelon to household income of smallholders. The study reveals that all the buyers were women and 97% of the producers were men indicating a male dominance in cultivating the crop. Overwhelming majority (73%) producers did not have formal education. Average household size was found to be 13, which is higher than the 6.1 recorded in the 2010 census data. In order of hierarchy, the livelihoods of famers were crop farming, livestock farming, fishing and trading. Family labour was the leading source of farm labour at 32.5% followed by hired labour at 31.7%. The production volume of watermelon was found to be declining from an average of 17 donkey carts in 2009 to 12.2 in 2013. This was attributed to low access to markets.55.8% and 30% of producers indicated incomes from watermelon cultivation formed very significant and significant portions house hold incomes respectively. The study revealed that personal characteristics of smallholders such sex had no influence access to service providers and farm size. Formal educational and marital status of respondents did not have influence on farm sizes of watermelon farmers. The study established that generally, weak relationship exist between watermelon farmers and other value chain actors such as MoFA, financial institutions, input dealers and buyers.